2004 IEEE International Conference on Mobile Ad-Hoc and Sensor Systems (IEEE Cat. No.04EX975)
DOI: 10.1109/mahss.2004.1392185
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking block ciphers for wireless sensor networks

Abstract: Choosing the most storage-and energy-efficient block cipher specifically for wireless sensor networks (WSNs) is not as straightforward as it seems. To our knowledge so far, there is no systematic evaluation framework for the purpose. In this paper, we have identified the candidates of block ciphers suitable for WSNs based on existing literature. For evaluating and assessing these candidates, we have devised a systematic framework that not only considers the security properties but also the storage-and energy-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…The evaluation results showed that Rijndael is suitable for high-security and energy-efficiency requirements while MISTY1 is suitable for good storage and energy efficiency. The evaluation results in [60] disagreed with the work in [8] in which RC5 was selected as the encryption/decryption scheme, and with the work in [22] in which RC6 was selected. The work in [60] provides a good resource for deciding which symmetric algorithm should be adopted in sensor networks.…”
Section: Symmetric Key Cryptography In Wsnscontrasting
confidence: 80%
See 1 more Smart Citation
“…The evaluation results showed that Rijndael is suitable for high-security and energy-efficiency requirements while MISTY1 is suitable for good storage and energy efficiency. The evaluation results in [60] disagreed with the work in [8] in which RC5 was selected as the encryption/decryption scheme, and with the work in [22] in which RC6 was selected. The work in [60] provides a good resource for deciding which symmetric algorithm should be adopted in sensor networks.…”
Section: Symmetric Key Cryptography In Wsnscontrasting
confidence: 80%
“…They further evaluated six block ciphers, including RC5 and RC6 [56], Rijndael [50], MISTY1 [57], KASUMI [58], and Camellia [59] on IAR Systems' MSP430F149 in [60]. The benchmark parameters were code, data memory, and CPU cycles.…”
Section: Symmetric Key Cryptography In Wsnsmentioning
confidence: 99%
“…Many research papers [3,6,7] analyze encryption algorithms for wireless sensor networks exclusively with reference to speed and code size while only a few [8] address the energy consumption of software based implementations. However, the ultra-low power applications we are envisioning, do not provide enough power for running cryptographic algorithms on general purpose microprocessors.…”
Section: Motivationmentioning
confidence: 99%
“…In [7] the authors present a detailed benchmark on block ciphers for wireless sensor networks. They consider security properties, storage and energy-efficiency of a set of candidates: RC5, RC6, Rijndael, MISTY1, KASUMI and Camellia.…”
Section: Related Workmentioning
confidence: 99%